Exploring the "Uneconomic Region" of the Production Function - Borts, G. H.; Mishan, E. J. (Review of Economic Studies, 1962)
G. H. Borts, E. J. Mishan; Exploring the “Uneconomic Region” of the Production Function1, The Review of Economic Studies, Volume 29, Issue 4, 1 October 196